Occurrence of Fusarium species in asymptomatic barley plants grown in field conditions under differential phosphate regimes - Echeverria, Mariela (2018)
Occurrence of genus Fusarium as endophytes in roots of healthy barley plants cultivated in fields under two levels of phosphorous (P) was examined. F. avenaceum, F. graminearum, F. konzum, F. oxysporum, F. sacchari, F. scirpi, F. solani were isolated from asymptomatic surface sterilized root tissues. F. konzum and F. solani were only present in the roots of fertilized plants, whereas F. sacchari was present in unfertilized plants. F. scirpi was isolated in highest frequency and relative density, and was higher under P deficiency suggesting that P availability would determinate the occurrence of this species, suggesting the possibility of their association with stressed plants. This is the first report on the occurrence of Fusarium spp. as endophytes in healthy barley plants. However, it remains to be determined whether Fusarium spp. isolated are nonpathogenic forms and beneficial to barley plants or latent pathogens that could produce disease symptoms in other conditions.